ASA classification and surgical severity grading used to identify a high‐risk population, a multicenter prospective cohort study in Swedish tertiary hospitals. Issue 9 (16th June 2021) - Bartha, Erzsebet; Ahlstrand, Rebecca; Bell, Max; Björne, Håkan; Brattström, Olof; Helleberg, Johan; Nilsson, Lena; Semenas, Egidijus; Kalman, Sigridur
Abstract : Background: Identification of surgical populations at high risk for negative outcomes is needed for clinical and research purposes. We hypothesized that combining two classification systems, ASA (American Society of Anesthesiology physical status) and surgical severity, we could identify a high‐risk population before surgery. We aimed to describe postoperative outcomes in a population selected by these two classifications system. Methods: Data were collected in a Swedish multicentre, time‐interrupted prospective, consecutive cohort study. Eligibility criteria were age ≥18 years, ASA ≥3, elective or emergent, major to Xmajor/complex (Specialist Procedure Codes used in United Kingdom), gastrointestinal, urogenital or orthopaedic procedures. Postoperative morbidity was identified by the Postoperative Morbidity Survey on postoperative days 3 ± 1, 7 ± 1, 10 + 5 and graded for severity by the Clavien‐Dindo system. Mortality was assessed at 30, 180 and 360 days. Results: Postoperative morbidity was 78/48/47 per cent on postoperative days 3/7/10. Majority of morbidities (67.5 per cent) were graded as >1 by Clavien‐Dindo. Any type of postoperative morbidity graded >1 was associated with increased risk for death up to one year. The mortality was 5.7 per cent (61/1063) at 30 days, 13.3 per cent (142/1063) at 6 months and 19.1 per cent (160/1063) at 12 months. Conclusion: Severity classification as major to Xmajor/complex and ASA ≥3 could be used to identify a high‐risk surgical population concerning postoperative morbidity and mortality before surgery. Combining the two systems future electronic data extraction is possible of a high‐risk population in tertiary hospitals.